2019
DOI: 10.1523/jneurosci.2668-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

The Large-Scale Organization of Gestures and Words in the Middle Temporal Gyrus

Abstract: The middle temporal gyrus (MTG) has been shown to be recruited during the processing of words, but also during the observation of actions. Here we investigated how information related to words and gestures is organized along the MTG. To this aim, we measured the BOLD response in the MTG to video clips of gestures and spoken words in 17 healthy human adults (male and female). Gestures consisted of videos of an actress performing object-use pantomimes (iconic representations of object-directed actions; e.g., pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…At the same time, Hafri et al (2017) demonstrated that it is possible to decode actions across stimulus format in the posterior LOTC, in line with the view that action-related representations in this area does not necessarily require visual motion. Together, our findings suggest that this area captures semantic aspects of actions at higher-order visual levels, whereas anterior portions of the left LOTC might capture these aspects at stimulus-independent or verbal levels of representation (see also Lingnau and Downing, 2015 and Papeo et al, 2019).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…At the same time, Hafri et al (2017) demonstrated that it is possible to decode actions across stimulus format in the posterior LOTC, in line with the view that action-related representations in this area does not necessarily require visual motion. Together, our findings suggest that this area captures semantic aspects of actions at higher-order visual levels, whereas anterior portions of the left LOTC might capture these aspects at stimulus-independent or verbal levels of representation (see also Lingnau and Downing, 2015 and Papeo et al, 2019).…”
Section: Discussionmentioning
confidence: 56%
“…Together, the results of the multiple regression RSA obtained for the different models are in line with the view that the LOTC hosts a variety of different, partially overlapping representations of action components that are likely to be integrated flexibly according to task demands (see also Lingnau and Downing, 2015). Multiple, possibly overlapping basic dimensions have been proposed to underlie the organization of these different action components within the LOTC, among them the input modality (visual versus non-visual; Lingnau and Downing, 2015; Papeo et al, 2019), the presence and orientation of a person, and the directedness of actions toward persons or other targets (Wurm et al, 2017; Wurm and Caramazza, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…These could be related to fewer resources of the audiovisual integration cortices allocated to visual cortices of the contralateral hemisphere in a resting state, with more resources allocated to enhance ipsilateral audiovisual processing. Interestingly, the intermediate region of the left middle temporal gyrus, which was found to be sensitive to words and emblems ( Papeo et al, 2019 ), demonstrated lower ALFF values in the UM group. This finding suggests that audiovisual plasticity may be region-specific, as different regions of visual processing (fusiform and middle temporal gyrus) differ in spontaneous regional activity in the resting state.…”
Section: Discussionmentioning
confidence: 99%
“…The angular gyrus has a wide range of functional relationships with many brain regions and is called a connection hub because of its functionality 40 . Similarly, the precentral gyrus was suggested to be involved in executing voluntary motor movements 41 and the middle temporal gyrus to be involved in actions and word meaning processing 42 . As these areas are constituents of the CEN 41,42 , they may have induced over-focus on tasks and interference with eye contact.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the precentral gyrus was suggested to be involved in executing voluntary motor movements 41 and the middle temporal gyrus to be involved in actions and word meaning processing 42 . As these areas are constituents of the CEN 41,42 , they may have induced over-focus on tasks and interference with eye contact. In relation to the quality of the mother-child interaction, the IRS score was positively associated with both eye gaze and eye contact in mothers, although it was only associated with eye contact in children.…”
Section: Discussionmentioning
confidence: 99%